Development of Digital-Based Accounting Entrepreneurship to Improve the Capacity of Micro, Small, and Medium Enterprises - Nurfadila, Nurfadila; Ajmal, Ajmal; Putri, Rina Mulya Herani; Fradisha, Adhies (Advances in Community Services Research, 2026)
Purpose: This Community Service activity aims to increase the business capacity of MSME players through the development of digital-based accounting entrepreneurship, particularly in strengthening digital literacy, financial recording capabilities, and readiness to face digital transformation in Padanglampe Village. Research Design and Methodology: The program was implemented through counseling, practical training, and intensive mentoring for PKK groups and MSME actors. Participants were trained to use digital accounting applications to record transactions, monitor cash flow, and prepare financial reports. Evaluation was conducted through observation, participant feedback, and assessment of application usage skills before and after training. Findings and Discussion: The results show a significant improvement in the mastery of digital accounting applications. Participants can record transactions more neatly, accurately, and in a structured manner. Financial management has become more transparent, thereby supporting more accurate business decision-making. In addition, participants have begun to understand the importance of digitization in expanding marketing and improving business efficiency. Implications: This program has implications for strengthening MSME competitiveness through digital and accounting literacy, increasing income, and facilitating access to funding. Sustainable implementation is recommended to enhance the digital transformation of rural MSMEs.